Analisis Pengaruh Pemasaran Media Sosial Terhadap Keputusan Pembelian Pada Marketplace Tokopedia : Studi Kasus Mahasiswa Institut Teknologi Del - Ivan Octhavianus L.Gaol; Mariana Simanjuntak (BADAN PENERBIT STIEPARI PRESS, 2024)
This research focuses on Del Institute of Technology students and aims to analyze the impact of social media marketing on purchasing decisions in the Tokopedia marketplace. In today's digital era, social media has become an important tool in marketing strategies, and it is important to understand its influence on purchasing decisions. This research uses a descriptive method with a quantitative approach. This data was collected through a questionnaire distributed to 35 students who are active on social media and have purchased products on Tokopedia at least once in the last six months. Data analysis was conducted using IBM SPSS software. The findings show that four social media marketing variables have a significant impact on students' purchasing decisions: content, interaction, use of influencers, and promotion. Interesting and informative content, responsive interactions, use of trusted influencers, and attractive promotions proved effective in increasing purchasing decisions. The conclusion of this study shows that an effective social media marketing strategy can increase purchasing decisions on Tokopedia. Based on these findings, some practical recommendations are made for Tokopedia to improve content quality, engagement, influencer selection, and advertising offers. This study also has limitations in sample size and population coverage, and it is recommended to conduct further research with larger samples and additional variables to support the results.